Scientific Learning Based on Tri Hita Karana on Pancasila Profile Students of Early Childhood - Rasmini, Ni Wayan; Karta, I Wayan (Universitas Pendidikan Ganesha, 2024)
Nowadays there is incompatibility with moral ethics and Pancasila values through the media. The emergence of bad behavior such as violence in the name of religion, bullying at school and outside school, student brawls, sexual harassment between school friends, theft, and bullying in the media, can become role models for children's behavior if not dealt with immediately. This study aims to analyze the effect of scientific learning based on Tri Hita Karana on the profile of Pancasila early childhood students. This study uses the experimental design for 50 early childhood children (5-6 years). Data was collected using observation guidelines that had been tested for content validity to observe the children's participation. The score data obtained for each variable was transformed to a scale of 100. The data in the form of percentages were analyzed for the normality of the data distribution and declared normal, and the linearity analysis of the regression line was declared linear. Hypothesis testing data analysis techniques apply simple regression and multiple regression. The error level used is 0.05. It was found that scientific learning based on Paluhuran, Pawongan, and Palemahan positively affected the profile of Pancasila students. Taken together, scientific learning based on Tri Hita Karana positively affects the profile of Pancasila early childhood students. It is hoped that all parties involved in the project to strengthen the profile of Pancasila early childhood students will apply scientific learning based on Paluhuran, Pawongan, and Palemahan holistically and integratively.